2017
DOI: 10.1111/1556-4029.13507
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lip Prints on Different Supports Using a Batch Image Processing Algorithm and Image Superimposition

Abstract: This study aimed to develop and to assess an algorithm to facilitate lip print visualization, and to digitally analyze lip prints on different supports, by superimposition. It also aimed to classify lip prints according to sex. A batch image processing algorithm was developed, which facilitated the identification and extraction of information about lip grooves. However, it performed better for lip print images with a uniform background. Paper and glass slab allowed more correct identifications than glass and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 24 publications
(40 reference statements)
0
31
0
2
Order By: Relevance
“…Although some researchers claimed high success rate in the detection of gender based on the lip print pattern type, a number of studies reported that there was no statistically significant difference between male and female lip print patterns [18,23,24]. Analysis of lip patterns for sex estimation can be a subjective process which must be performed with great caution, since a false estimation can prejudice a forensic case [25].…”
Section: Discussionmentioning
confidence: 99%
“…Although some researchers claimed high success rate in the detection of gender based on the lip print pattern type, a number of studies reported that there was no statistically significant difference between male and female lip print patterns [18,23,24]. Analysis of lip patterns for sex estimation can be a subjective process which must be performed with great caution, since a false estimation can prejudice a forensic case [25].…”
Section: Discussionmentioning
confidence: 99%
“…A queiloscopia é um método de identificação humana, onde são analisados, os sulcos labiais, suas disposições, as comissuras labiais e a espessura labial do indivíduo (Herrera, Fernandes & Serra, 2013;Herrera, Fernandes & Serra, 2018;Caldas, Magalhaes & Afonso, 2007). Ayuba et al (2019) afirmam que o padrão de impressão labial e a espessura dos lábios variam entre as populações; essa variação pode ajudar em investigações criminais e forenses.…”
Section: Queiloscopiaunclassified
“…Diferentes métodos para a identificação humana são utilizados pelos odontolegistas, sendo alguns deles: exame de registros odontológicos, que confronta a documentação odontológica prévia de um suspeito com o indivíduo a ser identificado, por comparação de exames radiológicos (Page et al, 2018), tomográficos e clínicos, análise de modelos de gesso, dos dados dos tratamentos realizados com aspectos da cavidade bucal da vítima (Afify et al, 2014); marcas de mordida (Freeman, Senn & Arendt, 2005); análise dos seios da face (Bangi et al, 2017) ; análise de saliva (Tsai et al, 2018); análise de rugas palatinas (Santos, Fernandes & Serra, 2011;Poojya et al, 2015); estimativa de idade por estágios de mineralização dentária (Bleka et al, 2019),impressões labiais (Sharma, Saxena & Rathod, 2009;Herrera, Fernandes & Serra, 2013;Herrera, Fernandes & Serra, 2018) e marcas de orelha (Silva, Fernandes & Serra, 2012).…”
Section: Introductionunclassified
“…Future endeavors will involve the exploration of other anatomical organs and parts, with the potential for I&A to fulfill essential biometric features (Table 4). These domains include, but are not limited to, finger-vein patterns [15], foot-printing [18], dorsal finger pattern [19], lip-printing [20], and tongue-printing [21].…”
Section: Reviewmentioning
confidence: 99%